"Next Generation EU" Cities Local Communities in a Post-Pandemic Future - Boni, Anna Lisa (ISPI Publications, 2022)
As the world enters a new year, the Covid-19 pandemic is still upsetting our daily lives. And as 75% of EU citizens live in urban areas, cities are the most prominent stage both for responding to the health crisis, and for seizing opportunities to recover and move forward. Meanwhile, in 2020, EU countries agreed to Next Generation EU, a €750 billion recovery package that represents a once-in-a-generation opportunity. This report argues that cities should be given more say over how post-pandemic national recovery plans pan out between here and 2026, when all projects are supposed to be wrapping up. Indeed, the success of the EU recovery plans will hinge upon what cities do, or they don't do over the next five years. How are cities rethinking their role within the "twin" green and digital transitions? How can they achieve gender parity, reduce inequalities, and preserve a vibrant cultural life?